Anaerobic curable composition

By using a composition containing unencapsulated liquid anaerobic curable monomers and solid components with specific functional groups, the problem of difficulty in keeping the composition in situ after dispensing in the prior art is solved, and stable curing and efficient use of the composition is achieved.

CN114026190BActive Publication Date: 2025-04-22HENKEL KGAA
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202080045437.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-21
Filing Date
2020-06-17
Publication Date
2025-04-22
Estimated Expiration
2040-06-17

AI Technical Summary

Technical Problem

Existing anaerobic curable compositions are difficult to remain in place after dispensing, and compositions in liquid form may cause contamination and incomplete adhesion upon use.

Method used

Compositions containing unencapsulated liquid anaerobic curable monomers and solid components with (meth)acrylate functional groups are employed, which are in particulate form, have a melting temperature of about 50°C to 90°C and account for 15% to 50% of the total weight of the composition. The composition can be used as a flowable paste at low temperatures and melts the solid components by heating and then cools to form a solid form.

Benefits of technology

The composition is achieved to remain in place after dispensing, avoiding the problems of contamination and incomplete bonding, while providing fast finger drying time and high viscosity liquid/paste handling and dispensing convenience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114026190B_ABST
    Figure CN114026190B_ABST
Patent Text Reader

Abstract

The present invention relates to an anaerobic curable composition, comprising: (a) an unencapsulated liquid anaerobic curable monomer forming a liquid phase; (b) a solid component dispersed as a solid phase in the liquid phase formed by the unencapsulated liquid anaerobic curable monomer; wherein the solid component has a (meth)acrylate functional group and: (i) is in the form of particles, wherein the particles have a particle size in the range of about 80 pm to about 300 pm; and (ii) has a melting temperature of about 50° C. to about 90° C.; and (c) a curing component for curing the anaerobic curable composition in the liquid phase. The anaerobic curable composition can be easily applied to a substrate such as a threaded fastener or other parts in its flowable form and then converted into an anaerobic curable composition in a solid form.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to anaerobically curable compositions. In particular, the present invention relates to anaerobically curable compositions that are easily dispensed but remain in place. Background Art

[0002] Anaerobic curable compositions are generally well known. See, for example, RD Rich, "Anaerobic Adhesives" in Handbook of Adhesive Technology, 29, 467-79, A. Pizzi and KL Mittal, eds., Marcel Dekker, Inc., New York (1994), and references cited therein. Their uses are widespread, and new applications are constantly being developed.

[0003] Anaerobic adhesive systems are those that are stable in the presence of oxygen but polymerize in the absence of oxygen. Polymerization is initiated by the presence of free radicals, usually generated by peroxide compounds. Anaerobic adhesive compositions are well known for their ability to remain in a liquid, unpolymerized state in the presence of oxygen and cure to a solid state when oxygen is excluded.

[0004] Anaerobic adhesive systems often include resin monomers derived according to known urethane chemistry terminated with polymerizable acrylates such as methacrylates, ethyl acrylates, and chloroacrylates [e.g., polyethylene glycol dimethacrylate and urethane-acrylates (e.g., U.S. Pat. No. 3,425,988 (Gorman)]. Other ingredients typically present in anaerobically curable adhesive compositions include: initiators, such as organic hydroperoxides, such as cumene hydroperoxide, t-butyl hydroperoxide, and the like; accelerators to increase the rate at which the composition cures; and stabilizers, such as quinones or hydroquinones, which are included to help prevent premature polymerization of the adhesive due to decomposition of the peroxide compound.

[0005] Desirable cure inducing compositions for inducing and promoting anaerobic cure may include one or more of saccharin, toluidine (e.g., N,N-diethyl-p-toluidine ("DE-pT") and N,N-dimethyl-o-toluidine ("DM-oT")), and acetophenylhydrazine ("APH"), with maleic acid. See, e.g., U.S. Pat. Nos. 3,218,305 (Krieble), 4,180,640 (Melody), 4,287,330 (Rich), and 4,321,349 (Rich).

[0006] Saccharin and APH are used as standard cure accelerator components in anaerobic adhesive cure systems. In fact, many of the Brand anaerobic adhesive products use either saccharin alone or a combination of saccharin and APH.

[0007] Anaerobically curable adhesive compositions also typically include a chelating agent, such as ethylenediaminetetraacetic acid (EDTA), to chelate metal ions.

[0008] For processing purposes, it is desirable that the anaerobically curable adhesive composition be easily dispensed but remain in place once dispensed. One of the problems that arise is that for ease of dispensing, it is desirable to have anaerobically curable adhesive composition in liquid form. Flowable liquids are easy to dispense. However, if the composition is liquid and flowable, it may be a problem to keep the composition on the substrate on which it is dispensed. Therefore, what is desired for dispensing may become a problem for disposal later.

[0009] Even though the anaerobically curable composition may dry out somewhat, such as by evaporation (either by being dried, or by being allowed to dry for a period of time), the material generally remains wet and tacky. This can lead to potential contamination of anything that comes in contact with the item to which the material has been applied, as well as unwanted removal of the applied material. The latter problem can compromise the integrity of any bond or seal subsequently formed with the anaerobically curable composition, as insufficient amounts may remain to form the desired bond or seal.

[0010] Of course, where the liquid carrier material is itself a liquid monomer, it will remain in its liquid form until when it is anaerobically cured. Thus, even though these compositions may be applied to a substrate awaiting exposure to anaerobic conditions, they will remain wet or at least tacky until cured.

[0011] In the past, additional components (such as thickeners) have been added to the material to make it less fluid, but because the other components are liquids, the overall composition still remains somewhat flowable and / or tacky.

[0012] Adhesive tape products already exist, e.g. 249 Quicktape TM The product consists of a liquid anaerobic threadlocker sandwiched between two films of a non-reactive polyamide / polyurethane film.

[0013] Compositions, including those suitable for use in threadlocking applications, can be applied dry to the touch but with post-curing anaerobic functionality. To achieve this, additional components are often used.

[0014] In some cases, a dry-to-touch form is achieved by using a curing mechanism. For example, a first curing mechanism may form a dry-to-touch form to hold the composition in place on an article, and a second (anaerobic) curing mechanism may be activated later to achieve curing, such as to achieve thread locking.

[0015] For example, European Patent No. 0 077 659 (Thompson) describes a pre-applied polymerizable fluid for sealing and locking engineering parts. The composition has two curing mechanisms and two curing reactions occur. The first mechanism is UV curing. A sunscreen is dispersed in the fluid so that the fluid becomes substantially opaque to radiation. After the fluid is applied to the part, it is exposed to UV radiation and then a coating is formed, thereby producing a surface layer, which is a dry, non-sticky outer skin. The subcutaneous fluid (due to the sunscreen) is not affected by the radiation and remains generally liquid. When the part is screwed into another part, the surface layer breaks, triggering a second polymerization (e.g., free radical polymerization) and a second curing reaction occurs. The second polymerization mechanism works to lock the threads together. In Thompson, only the epidermis is formed in the first polymerization, and the remainder of the composition remains fluid under the epidermis. Therefore, there is a risk that the epidermis may be damaged and the fluid composition may leak during the handling of the coated engineering parts.

[0016] European Patent No. 0 548 369 (Usami) describes a pre-applied adhesive composition for application to the threaded contact surface of a screw. The composition comprises a light-hardening adhesive in which a second curable composition is dispersed. The second curable composition comprises a microencapsulated reactive monomer / activator / initiator.

[0017] International Patent Publication WO2004 / 024841 A2 (Haller) describes a curable composition for application to threaded articles. The composition comprises a dispersion of a first curing mechanism component and (ii) a second curing mechanism component together with (iii) a thickener component, wherein the first curing mechanism components comprise (a) a (meth)acrylate functional monomer component, (b) a (meth)acrylate functional oligomer component and (c) a photoinitiator component, and the (ii) second curing mechanism components comprise (e) an amine component and (f) an encapsulated epoxy resin component. The photoinitiator component is suitable for achieving a first cure through the depth of the composition applied to the threaded article upon irradiation of the composition, thereby forming an adhesive matrix, wherein the second curing mechanism components are dispersed throughout the matrix.

[0018] The English abstract of Chinese patent publication CN102558490 appears to disclose a hot-melt prepolymer, which is a carbamate or polyurethane (meth)acrylate prepolymer with (meth)acryloyl terminal groups. The melting point of the prepolymer is 50-80°C. An anaerobic adhesive is prepared from the hot-melt prepolymer, a monomer containing at least one acrylate group or methacryloyl group, a promoter, a stabilizer and an initiator. A liquid monomer is combined with the prepolymer to form a gel.

[0019] The applicant's international patent publication number WO 2017 / 068196 describes an anaerobic curable composition comprising an anaerobic curable component, which is a combination of a solid resin component and a solid anaerobic curable monomer. A curing component for curing the anaerobic curable component is included. The composition is solid and has a melting point in the range of 30°C to 100°C. The composition is dry to the touch and can be used to form articles such as tapes, elongated filaments, gaskets, and patches.

[0020]

[0006] Despite the state of the art, it would be desirable to provide alternative anaerobically curable compositions suitable for typical end-use applications including threadlocking applications. Summary of the invention

[0021] In one aspect, the present invention provides an anaerobically curable composition comprising:

[0022] (a) an unencapsulated liquid anaerobically curable monomer forming a liquid phase;

[0023] (b) a solid component dispersed as a solid phase in a liquid phase formed from an unencapsulated liquid anaerobically curable monomer;

[0024] wherein the solid component has (meth)acrylate functionality and:

[0025] (i) in the form of particles, wherein the particles have an average particle size in the range of about 80 μm to about 300 μm; and

[0026] (ii) having a melting temperature of about 50°C to about 90°C; and

[0027] (c) a curing component for curing the anaerobic curable composition in the liquid phase.

[0028] The unencapsulated liquid anaerobic curable monomer may be present in an amount of about 10 wt % to about 50 wt %, for example about 10 wt % to about 40 wt %, such as about 10 wt % to about 30 wt %, based on the total weight of the composition.

[0029] The solid component may be present in an amount of about 15 wt% to about 50 wt%, for example about 30 wt% to about 45 wt%, based on the total weight of the composition.When the solid component is dispersed in the liquid phase, it is in the form of particles.

[0030] The solid component is reactive - it participates in the anaerobic curing reaction.

[0031] The curing component / initiator is present in an amount of about 4 wt % to about 6 wt %, based on the total weight of the composition.

[0032] The anaerobic curable composition of the present invention may further comprise about 10% to about 30% by weight of propoxylated bisphenol A fumarate polyester, based on the total weight of the composition dissolved in the liquid phase. This component imparts the desired viscosity when the composition of the present invention is in the form of a paste, and also imparts the desired physical properties of the solid form. Other viscosity modifiers may be used, such as acrylic resins (e.g., available under the trade name Those available from Lucite International). Silica is also possible. However, it is desirable to use propoxylated bisphenol A fumarate polyester. In general, the amount of viscosity modifier (including propoxylated bisphenol A fumarate polyester) is generally from about 10% to about 30% by weight based on the total weight of the composition dissolved in the liquid phase.

[0033] The solid component desirably comprises a solid anaerobically curable monomer having a melting point of about 50°C to about 90°C.

[0034] Optionally, the solid component comprises a solid resin having a melting point of about 50°C to about 90°C.

[0035] The solid resin has (meth)acrylate functional groups.

[0036] In one form, the composition of the invention is a flowable paste having a viscosity at 25°C of about 40,000 to 500,000 mPa·s, for example about 60,000 to about 180,000 mPa·s, such as about 75,000 to about 125,000 mPa·s as determined by ASTM D4287.

[0037] The anaerobically curable composition of the present invention may be provided in a solid form formed by heating the composition according to any one of the preceding claims so that the solid components melt into a molten form and mix with an unencapsulated liquid anaerobically curable monomer to form a mixture; and passively or actively cooling the mixture into a solid form.

[0038] The present invention also relates to a substrate to which the anaerobically curable composition of the present invention is applied in the form of a paste.

[0039] The present invention also relates to a substrate having applied thereto the anaerobically curable composition in solid form.

[0040] The present invention also provides a method for preparing anaerobically curable composition, wherein the anaerobically curable composition comprises

[0041] (a) an unencapsulated liquid anaerobically curable monomer forming a liquid phase;

[0042] (b) a solid component dispersed as a solid phase in a liquid phase formed from an unencapsulated liquid anaerobically curable monomer;

[0043] wherein the solid component has (meth)acrylate functional groups and:

[0044] (i) in the form of particles, wherein the particles have a particle size in the range of about 80 μm to about 300 μm; and

[0045] (ii) having a melting temperature of about 50°C to about 90°C; and

[0046] (c) a curing component for curing the anaerobic curable composition in the liquid phase,

[0047] The method comprises the step of dispersing the solid component in the liquid phase.

[0048] In the method of the present invention, it is desirable to add the solidifying component after the step of dispersing the solid component in the liquid phase.

[0049] Desirably, the solidifying component is added in microencapsulated form.

[0050] The present invention also provides a method for applying the anaerobically curable composition of the present invention to a substrate, the method comprising the steps of:

[0051] (a) formulating the composition into a flowable composition;

[0052] (b) applying the flowable composition to a substrate;

[0053] (c) heating the composition so that the solid components melt into a molten form and mix with the unencapsulated liquid anaerobically curable monomer to form a mixture; and

[0054] (d) passively or actively cooling the mixture into a solid form on the substrate.

[0055] The present invention also relates to an assembly comprising a first substrate and a second substrate bonded together by utilizing any composition according to any one of claims 1 to 9.

[0056] The compositions of the present invention may be in two different forms.

[0057] At a temperature below the melting point of the solid component (e.g., a temperature below 50° C.) and therefore at ambient temperature, the composition is flowable, forming a paste having a viscosity at 25° C. of about 40,000 to 500,000 mPa·s, e.g., about 60,000 to about 180,000 mPa·s, such as about 75,000 to about 125,000 mPa·s as determined by ASTM D4287. The solid component is solid and remains dispersed in the liquid phase. In this first paste form formed by the solid dispersed in the liquid phase, the composition is anaerobically curable but flowable. At a temperature below the melting point of the solid component, the solid component is insoluble in the liquid phase.

[0058] Once the composition of the present invention is heated to or above the melting point of the solid component, for example at or above a temperature of 50°C, and therefore well above ambient temperature, the solid component melts into a liquid and moves into the liquid phase, so there is now a single merged phase. In its molten form, the solid component is miscible with the liquid phase. Once the merged material cools below the melting point of the solid component, the composition does not return to a flowable paste form, but becomes solid. For example, it may be a waxy solid.

[0059] In this second form, the solid components and the unencapsulated liquid anaerobically curable monomer are no longer in different phases, but are in a single solid phase. The composition remains uncured, but is still anaerobically curable, yet solid.

[0060] When the solid component melts, the solid component is compatible with the liquid phase and combines well. It does not separate from the liquid phase.

[0061] When the composition is cooled, the composition changes to a solid form (from a paste form before heating) (to produce a homogenous solid form of the product).

[0062] The solid form may be in the form of particles, such as a powder. The powder form is substantially dry so that the particles do not stick / clump together.

[0063] The solid component may be a combination of suitable materials.

[0064] The solid component is curable / reactive. The solid component participates in the anaerobic curing reaction and is itself anaerobically curable.

[0065] Thus, all reactive components - whether liquid or solid components of the composition - can participate in the anaerobic curing reaction.

[0066] In the present invention, the particle size is determined by laser diffraction according to ASTM E2651-13.

[0067] Melting and resolidification can be measured by DSC (Differential Scanning Calorimetry).

[0068] The invention disclosed herein relates to a new anaerobic curable composition having a new physical form. It is an anaerobic adhesive composition that can be used to achieve a solid coating that is dry to the touch for pre-applied applications. The anaerobic curable composition comprises a curable solid reactive component (optionally with a non-reactive component) suspended in a liquid reactive monomer to combine to form a paste. At the melting point of the solid, the paste is converted to a liquid as the solid melts, which then forms a solid material upon cooling. When the composition is heated and the solid material melts, it does not revert to a paste form due to the mixing of the solid and liquid materials.

[0069] This new anaerobic product form can be manufactured, handled and dispensed as a high viscosity liquid / paste, but is easily converted to a solid material by heating. It is designed to address handling, processing and stability issues.

[0070] Of course, it is flowable and anaerobically curable in its first form, and then solid but anaerobically curable in its solid form. In addition, the viscosity of its first form is 75,000 to 500,000 mPa s at 25°C (or in fact in other viscosity ranges disclosed herein) means that it can be dispensed onto a substrate in a curable and flowable form. This allows for diversity in application. Once heated on a substrate, the composition can be converted into a solid form or the composition can be solidified into a solid form. The solid form is still anaerobically curable. The solid form has the advantage of being non-flowable, so the anaerobically curable composition remains on the substrate. The initial flowable composition can be converted into a solid composition, so the flowable composition can be considered a plastisol.

[0071] For example, the anaerobically curable composition can be easily applied to a substrate (e.g., a threaded fastener or other part) in its flowable form and then converted to a solid anaerobically curable composition. Once solid, the risk of the anaerobically curable composition causing handling problems because the material is flowable / liquid is eliminated. Therefore, equipment used to handle substrates and other substrates that come into contact with any coated substrate are less likely to be contaminated by transfer of the anaerobically curable composition from physical contact with the equipment and / or other substrates.

[0072] An object of the present inventors is to develop an anaerobically curable composition (e.g., an anaerobic adhesive) that can be applied to a substrate (e.g., a threaded fastener) with a rapid dry-to-touch time, thereby allowing for rapid turnover of the substrate, particularly by eliminating drying time.

[0073] This is of interest for articles (e.g., substrates) that are coated with anaerobically curable compositions for later use. That is, they are coated with the composition of the invention so that they have a pre-applied anaerobically curable composition in situ for (later) - typically off-site - use.

[0074] The market for pre-applied anaerobic products is currently served by water-based and solvent-based products. These products are applied in specialized coating centers using large footprint equipment. For example, Henkel's The product is a water-based anaerobic adhesive technology. Some of these prior art compositions are two-part or three-part formulations that are mixed at the application site and applied to a large number of threaded fasteners using specialized equipment. The water (or solvent) content of the formulation is then removed over a period of several hours by using large drying ovens to provide threaded bolts with pre-applied adhesive.

[0075] In the present invention, an anaerobic adhesive is provided which contains solid elements that melt at reasonably low temperatures (e.g. 55-80°C), can be applied to threaded parts in molten form, and will cool rapidly to leave a solid coating on the part. This eliminates the need for large drying ovens and dedicated coating centers, and can provide a pre-applied solution, for example for smaller scale users.

[0076] The room temperature paste form is straightforward for manufacture and handling of the composition, including bottling / packaging.

[0077] Furthermore, the compositions of the invention may also be in solid form, for example in a container from which they are later removed for use rather than being pre-applied.

[0078] The paste form may be dispensed in paste form from a dispensing package or cartridge package.

[0079] As described herein, the composition can be converted to a solid form in a pre-application form, so that an article manufactured at a first location for use at a second location can have the composition in solid form pre-applied to a substrate. Alternatively, the conversion to a solid form can occur at the location of dispensing / application to a substrate.

[0080] One advantage of the present invention is that the composition is formulated as a one-part composition, yet is anaerobically curable. When the composition of the present invention is subjected to a temperature of 22°C under ASTM: D1337, a storage stability of at least 12 months has been achieved. Some existing anaerobically curable compositions are formulated as at least two-part compositions because if they are formulated as a one-part composition, they are not storage stable / cured prematurely.

[0081] Another advantage of the present invention is that the composition dries quickly - no drying ovens or long drying times are required as with water-based or solvent-based compositions.

[0082] The compositions of the present invention are therefore well suited for smaller scale operations.

[0083] The compositions of the present invention allow for unique combinations of forms. For example, the compositions of the present invention can be sequentially transformed from a paste (in which solid particles are dispersed in a liquid phase) to a liquid (in which the solid particles are melted to mix with the liquid phase) to a solid (the composition solidifies upon cooling).

[0084] The unencapsulated liquid anaerobically curable monomer can be any liquid methacrylate; or acrylate; functionalized monomer. Any combination of unencapsulated liquid anaerobically curable monomers can be used.

[0085] The solid component is curable / reactive. The solid component participates in the anaerobic curing reaction and is itself anaerobically curable.

[0086] However, other components of the composition may be liquid or solid and may be non-reactive - they do not participate in the anaerobic curing reaction.

[0087] The solid component may be an anaerobically curable monomer in solid form, such as 2-methacryloyloxyethylphenylcarbamate - "2-MAPU".

[0088] The solid component may be a methacrylate-functionalized resin in solid form, for example a long-chain meth(acrylated)polyurethane having a molecular weight > 2000 g / mol.

[0089] The solid component may be any other solid powder material as long as, in general, it meets the above parameters.

[0090] Desirably, the solid component does not include polyethylene glycol, such as polyethylene glycol particles, which are inert in the anaerobic curing reaction.

[0091] It should be understood that the solid component can be any combination of those materials listed above, as long as overall it meets the parameters listed above.

[0092] The compositions of the present invention have many of the same end-use applications as conventional anaerobically curable compositions.

[0093] The composition of the invention can be applied in metal-metal bonding (e.g., threadlocking compositions) for securing, e.g., female threaded items to male threaded items, e.g., for securing nuts and bolts. The product cures when confined between closely fitting (e.g., metal) surfaces in the absence of air. It protects the threads from rust and corrosion, and from loosening due to shock and vibration.

[0094] The composition of the present invention is suitable for storage or handling, such as transportation, even when applied to a part. Such storage or handling does not adversely affect the integrity of the composition, such as when the composition is present as a coating.

[0095] Mating surfaces (e.g., flanges, such as in the automotive industry) have been sealed in the past by applying a liquid anaerobically curable composition to the face of one of the surfaces. The two surfaces (e.g., flange faces) are then assembled and the product is cured in the absence of oxygen to form a gasket and seal. The composition of the present invention can be applied to such mating surfaces in liquid or paste form. For example, it can be applied in paste form and then heated and converted to solid form.

[0096] Desirable cure-inducing components for inducing and promoting anaerobic cure may include one or more of saccharin, toluidine (e.g., N,N-diethyl-p-toluidine ("DE-pT") and N,N-dimethyl-o-toluidine ("DM-oT")), and acetophenylhydrazine ("APH"), with maleic acid. See, e.g., U.S. Pat. Nos. 3,218,305 (Krieble), 4,180,640 (Melody), 4,287,330 (Rich), and 4,321,349 (Rich).

[0097] Stabilizers such as quinone or hydroquinone may be included.

[0098] The unencapsulated liquid anaerobically curable monomer may be selected from any suitable anaerobically curable material (or any combination of such materials), including those listed below. Desirably, it is a liquid.

[0099] The anaerobically curable composition may have an anaerobically curable component based on a suitable (meth)acrylate component.

[0100] One or more suitable (meth)acrylate components may be selected from those (meth)acrylate monomers having the formula: 2 C=CGCO 2 R 8, wherein G may be hydrogen, halogen, or an alkyl group having 1 to about 4 carbon atoms, and R 8 It can be selected from alkyl, cycloalkyl, alkenyl, cycloalkenyl, alkaryl, aralkyl or aryl groups having from 1 to about 16 carbon atoms, any of which can be optionally substituted or interrupted by silane, silicon, oxygen, halogen, carbonyl, hydroxyl, ester, carboxylic acid, urea, carbamate, polyurethane, carbonate, amine, amide, sulfur, sulfonate and sulfone as appropriate.

[0101] One or more suitable (meth)acrylate monomers may be selected from multifunctional (meth)acrylate monomers, such as, but not limited to, difunctional or trifunctional (meth)acrylates, such as polyethylene glycol di(meth)acrylate, tetrahydrofuran (meth)acrylate and di(meth)acrylate, hydroxypropyl (meth)acrylate ("HPMA"), hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate ("TMPTMA"), diethylene glycol dimethacrylate, triethylene glycol dimethacrylate ("TRIEGMA"), tetraethylene glycol dimethacrylate, dipropylene glycol dimethacrylate, dipentyl glycol dimethacrylate, tetraethylene glycol (tetraethylene diglycol) diacrylate, diglycerol tetramethacrylate, tetramethylene dimethacrylate, ethylene glycol dimethacrylate ("ethylene glycol dimethacrylate"), and the like. dimethacrylate), neopentyl glycol diacrylate, trimethylolpropane triacrylate; and bisphenol-A mono- and di(meth)acrylates, such as ethoxylated bisphenol-A (meth)acrylate ("EBIPMA"); and bisphenol-F mono- and di(meth)acrylates, such as ethoxylated bisphenol-F (meth)acrylate.

[0102] For example, the anaerobic curable component may include (as an anaerobic curable monomer) bisphenol A dimethacrylate:

[0103]

[0104] It has a melting point of approximately 72°C to 74°C.

[0105] Still other (meth)acrylate monomers that may be suitable for use herein are silicone (meth)acrylate moieties ("SiMA") such as those taught and claimed in U.S. Pat. No. 5,605,999 (Chu), the disclosure of which is expressly incorporated herein by reference.

[0106] Other suitable monomers may be selected from polyacrylates represented by the following formula:

[0107]

[0108] Where R 4 is a group selected from hydrogen, halogen or an alkyl group having 1 to about 4 carbon atoms; q is an integer equal to at least 1, preferably an integer equal to 1 to about 4; and X is an organic group containing at least two carbon atoms and having a total bonding capacity of q+1. Regarding the upper limit of the number of carbon atoms in X, the monomers that can be used exist at essentially any value. However, in practice, the general upper limit is about 50 carbon atoms, such as desirably about 30, and desirably about 20.

[0109] For example, X can be an organic group of the formula:

[0110]

[0111] where Y 1 and Y 2 Each of is an organic group (e.g., a hydrocarbon group) containing at least 2 carbon atoms, desirably 2 to about 10 carbon atoms; and Z is an organic group (preferably a hydrocarbon group) containing at least 1 carbon atom, preferably 2 to about 10 carbon atoms. Other monomers may be selected from the reaction products of di- or trialkanolamines (e.g., ethanolamine or propanolamine) and acrylic acid, such as disclosed in French Patent No. 1,581,361.

[0112] Suitable oligomers having (meth)acrylate functional groups may also be used. Examples of such (meth)acrylate functional oligomers include those having the general formula:

[0113]

[0114] Where R 5 represents a group selected from hydrogen, an alkyl group having 1 to about 4 carbon atoms, a hydroxyalkyl group having 1 to about 4 carbon atoms, or

[0115]

[0116] Where R 4 is a group selected from hydrogen, halogen or an alkyl group having 1 to about 4 carbon atoms; R 6 is a group selected from hydrogen, hydroxyl or the following formula,

[0117]

[0118] m is an integer equal to at least 1, such as an integer from 1 to about 15 or greater, desirably an integer from 1 to about 8; n is an integer equal to at least 1, such as an integer from 1 to about 40 or greater, desirably an integer from about 2 to about 10; and p is 0 or 1.

[0119] Typical examples of acrylate oligomers corresponding to the above general formula include: di-, tri- and tetraethylene glycol dimethacrylates; di(pentylene glycol) dimethacrylate; tetraethylene glycol diacrylate; tetraethylene glycol di(chloroacrylate); diglycerol diacrylate; diglycerol tetramethacrylate; butanediol dimethacrylate; neopentyl glycol diacrylate; and trimethylolpropane triacrylate.

[0120] While diacrylates and other polyacrylates, particularly the polyacrylates described in the preceding paragraphs, may be desirable, monofunctional acrylates (esters containing one acrylate group) may also be used.

[0121] Suitable compounds may be selected from: cyclohexyl methacrylate, tetrahydrofurfuryl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, tert-butylaminoethyl methacrylate, cyanoethyl acrylate and chloroethyl methacrylate.

[0122] Another useful class of materials is the reaction product of a (meth)acrylate functionalized hydroxyl- or amino-containing material and a polyisocyanate in suitable proportions to convert all of the isocyanate groups to urethane or urea groups, respectively.

[0123] The (meth)acrylate urethane or urea thus formed may contain hydroxyl or amino functional groups on the non-acrylate portion thereof. (Meth)acrylates suitable for use may be selected from those of the formula:

[0124]

[0125] Where X is selected from --O-- and

[0126]

[0127] Where R 9 is selected from hydrogen or a lower alkyl group of 1 to 7 carbon atoms; R 7 is selected from hydrogen, halogen (such as chlorine) or alkyl (such as methyl and ethyl); and R 8 It is a divalent organic group selected from an alkylene group having 1 to 8 carbon atoms, a phenylene group and a naphthalene group.

[0128] These groups, when appropriately reacted with polyisocyanates, produce monomers of the general formula:

[0129]

[0130] wherein n is an integer from 2 to about 6; B is a polyvalent organic group selected from substituted and unsubstituted alkyl, alkenyl, cycloalkyl, cycloalkenyl, aryl, alkaryl, alkaryl and heterocyclyl, and combinations thereof; R 7 , R 8and X have the meanings given above.

[0131] Depending on the species of B, these (meth)acrylates with urea or urethane linkages can have molecular weights that place them in the oligomeric species (eg, about 1,000 to about 5,000 g / mol) or polymeric species (eg, about greater than 5,000 g / mol).

[0132] Of course, combinations of these (meth)acrylate monomers may also be used.

[0133] Desirably, the anaerobically curable component comprises at least one acrylate or methacrylate group.

[0134] Desirably, the anaerobic curable component comprises at least one selected from the group consisting of epoxy (meth)acrylates, urethane (meth)acrylates, urethane di(meth)acrylates, alkyl (meth)acrylates, octadecyl (meth)acrylates, isocyanurate (meth)acrylates, bisphenol-A-(meth)acrylates, ethoxylated bisphenol-A-(meth)acrylates, bisphenol-F-(meth)acrylates, ethoxylated bisphenol-F-(meth)acrylates, bisphenol-A-di(meth)acrylates, ethoxylated bisphenol-A-di(meth)acrylates, bisphenol-F-di(meth)acrylates, and ethoxylated bisphenol-F-di(meth)acrylates.

[0135] The compositions of the present invention may also contain other conventional components such as free radical initiators, free radical accelerators, free radical generation inhibitors, and metal catalysts (eg, iron and copper).

[0136] Many well-known free radical polymerization initiators can be added to the compositions of the present invention, including but not limited to hydroperoxides such as CHP, p-menthane hydroperoxide, tert-butyl hydroperoxide ("TBH"), and tert-butyl perbenzoate. Other peroxides include benzoyl peroxide, dibenzoyl peroxide, 1,3-bis(tert-butylperoxyisopropyl)benzene, diacetyl peroxide, 4,4-bis(tert-butylperoxy)butyl valerate, p-chlorobenzoyl peroxide, cumene hydroperoxide, tert-butyl isopropyl peroxide, tert-butyl perbenzoate, di-tert-butyl peroxide, diisopropyl peroxide, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane, 2,5-dimethyl-2,5-di-tert-butyl-peroxyhex-3-yne, 4-methyl-2,2-di-tert-butyl peroxypentane, and combinations thereof.

[0137] Such peroxide compounds are generally used herein in the range of about 0.1 to about 10 weight percent based on the total weight of the composition, with about 1 to about 5 weight percent based on the total weight of the composition being desirable.

[0138] If desired, the initiator component can be encapsulated. For example, the initiator component can be an encapsulated peroxide, such as encapsulated benzoyl peroxide ("BPO").

[0139] For example, for the composition of the present invention, an encapsulated material, such as a microencapsulated material, such as an initiator component which may be an encapsulated peroxide (e.g., encapsulated benzoyl peroxide), may be dispersed in the first paste form without heating. This is advantageous because the microencapsulated peroxide initiator BPO has a half-life of 1 hour at 92°C.

[0140] In paste form, microcapsules and other powdered solids are easily dispersed; no sedimentation, better stability.

[0141] The composition of the present invention may further comprise a thickener and / or a filler.

[0142] As mentioned above, it will be understood that the compositions of the present invention may contain non-reactive materials, including resins. Such components do not participate in the anaerobic curing reaction. They are non-reactive. However, such components may become part of the cured product into which other components have been incorporated during curing. Examples of such non-reactive materials include: fumed silica, polyethylene, PTFE, mica, polyamide wax, titanium dioxide, barium sulfate. BRIEF DESCRIPTION OF THE DRAWINGS

[0143] Embodiments of the present invention will be described by way of example only with reference to the accompanying drawings, in which:

[0144] Figure 1 is a graph showing the 24 hour cure strength of the composition of Example 2 on various threaded fasteners. DETAILED DESCRIPTION

[0145] Embodiments of the present invention will be described by way of example only in conjunction with the following:

[0146] Example 1 - Paste Formulation 4158-045.

[0147]

[0148] LID 6882 is a functional solid resin which is a difunctional methacrylated PU resin derived from semi-crystalline polyols. When it is micronized it has an average particle size of <100 μm.

[0149] The composition in the table above was combined with a solid monomer: 2-methacryloyloxyethylphenyl carbamate.

[0150] Example 2: Paste Formulation 4158-063

[0151]

[0152] LID 6882 is a functional solid resin which is a difunctional methacrylated PU resin derived from semi-crystalline polyols. When it is micronized it has an average particle size of <100 μm.

[0153] The composition in the table above was combined with a solid monomer: 2-methacryloyloxyethylphenyl carbamate.

[0154] Figure 1 is a graph showing the 24-hour cure strength of the composition of this example on various M10 threaded fasteners. The composition of this example was applied to an M10 bolt that had been heated to 90°C. The bolts used were made of stainless steel, zinc phosphate, zinc dichromate coated steel, brass, and black oxide coated mild steel. The paste was applied to the heated parts, where it melted and then cooled to form a solid waxy coating. The mating nut was combined with the coated part, the unseated assembly was cured for 24 hours, and the strength required to separate the assembled nut and bolt was thereafter estimated on a torque measuring device using ASTM D5649.

[0155] Example 3: Paste Formulation 4158-064

[0156]

[0157] Non-functional solid powder: polyethylene glycol with an average molecular weight of 8000 g / mol.

[0158] The composition in the table above was combined with a solid monomer: 2-methacryloyloxyethylphenyl carbamate.

[0159] When used herein in relation to the present invention, the words "comprise / comprising" and the words "have / include" are used to specify the presence of stated features, integers, steps or components, but do not preclude the presence or addition of one or more other features, integers, steps, components or groups thereof.

[0160] It should be understood that certain features of the present invention described in the context of separate embodiments for clarity may also be provided in combination in a single embodiment. Conversely, various features of the present invention described in the context of a single embodiment for brevity may also be provided individually or in any suitable sub-combination.

Claims

1. An anaerobic curable composition comprising: (a) an unencapsulated liquid anaerobic curable monomer that forms a liquid phase, wherein the unencapsulated liquid anaerobic curable monomer is present in an amount of 10 wt % to 40 wt % based on the total weight of the composition; (b) a solid component dispersed as a solid phase in a liquid phase formed by the unencapsulated liquid anaerobically curable monomer; wherein the solid component has (meth)acrylate functional groups and: (i) in the form of particles, wherein the particles have an average particle size in the range of 80 μm to 300 μm; (ii) has a melting temperature of 50°C to 90°C; and (iii) the solid component is present in an amount of 15 wt % to 50 wt % based on the total weight of the composition; and (c) a curing component for curing the reactive components in the anaerobic curable composition, wherein the curing component is present in an amount of 4 wt % to 6 wt % based on the total weight of the composition, wherein the composition further comprises 20 wt % of propoxylated bisphenol A fumarate polyester based on the total weight of the composition, and wherein the composition is a flowable paste having a viscosity at 25° C. of 75,000 to 125,000 mPa·s as measured by ASTM D4287.

2. The anaerobically curable composition of claim 1, wherein the unencapsulated liquid anaerobically curable monomer is present in an amount of 10 wt% to 30 wt%, based on the total weight of the composition.

3. The anaerobically curable composition of claim 1, wherein the solid component is present in an amount of 30 wt% to 45 wt% based on the total weight of the composition.

4. The anaerobically curable composition according to any one of claims 1 to 3, wherein the solid component comprises a solid anaerobically curable monomer having a melting point of 50°C to 90°C.

5. The anaerobically curable composition according to any one of claims 1 to 3, wherein the solid component comprises a solid resin having a melting point of 50°C to 90°C.

6. An anaerobically curable composition in solid form, formed by: heating the composition of any one of the preceding claims, thereby causing the solid component to melt into a molten form and mix with the unencapsulated liquid anaerobically curable monomer to form a mixture; and passively or actively cooling the mixture into a solid form.

7. A substrate having applied thereto the anaerobically curable composition according to any one of claims 1 to 5.

8. A substrate having applied thereto the anaerobically curable composition according to claim 6.

9. A method for preparing anaerobically curable composition, wherein the anaerobically curable composition comprises (a) an unencapsulated liquid anaerobic curable monomer that forms a liquid phase, wherein the unencapsulated liquid anaerobic curable monomer is present in an amount of 10 wt % to 40 wt % based on the total weight of the composition; (b) a solid component dispersed as a solid phase in a liquid phase formed by the unencapsulated liquid anaerobically curable monomer; wherein the solid component has (meth)acrylate functional groups and: (i) in the form of particles, wherein the particles have a particle size in the range of 80 μm to 300 μm; and (ii) has a melting temperature of 50°C to 90°C; and (iii) the solid component is present in an amount of 15 wt % to 50 wt % based on the total weight of the composition; and (c) a curing component for curing the reactive components in the anaerobic curable composition, wherein the curing component is present in an amount of 4 wt % to 6 wt % based on the total weight of the composition, wherein the composition further comprises 20 wt % of propoxylated bisphenol A fumarate polyester based on the total weight of the composition, and wherein the composition is a flowable paste having a viscosity at 25° C. of 75,000 to 125,000 mPa·s as measured by ASTM D4287; and The method comprises the step of dispersing the solid component in the liquid phase.

10. The method of claim 9, further comprising adding the solidifying component after the step of dispersing the solid component in the liquid phase.

11. The method according to claim 10, wherein the solidifying component is added in microencapsulated form.

12. A method of applying the anaerobically curable composition according to any one of claims 1 to 5 to a substrate, comprising the steps of: (a) formulating the composition into a flowable composition; (b) applying the flowable composition to a substrate; (c) heating the composition so that the solid components melt into a molten form and mix with the unencapsulated liquid anaerobic curable monomer to form a mixture; and (d) passively or actively cooling the mixture into a solid form on the substrate.

13. An assembly comprising a first substrate and a second substrate bonded together by utilizing the composition according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • A polymerisable fluid

    EP0077659A1

  • Adhesive composition

    EP0548369A1

  • FR1581361A

  • Accelerated anaerobic compositions and method of using same

    US3218305A

  • Polyurethane polyacrylate sealant compositions

    US3425988A